The Measurement of Performance skills of Primary Maternal Child Health Workers - An Indian Experiment - Mohanty N; Mohapatra S.C; Srivastava P; Gupta J.N.P (Wolters Kluwer Medknow Publications, 1994)
Research Questions: 1. What are the cognitive and psychomotor levels of Anganwadi Workers (AWW) regarding important aspects of maternal and child health? 2. Can these skills be improved by training with a self learning communication module? Objectives: (i) Identify and evaluate the level of intellectual and practical skills acquired by the AWWs on some areas of primary. health care like : detection of low birth weight (LBW) babies, weight of the baby, measurement of body temperature by thermometer, identification of diarrhoea and preparation of ORS, detection of high risk cases and referral. (ii) Develop and test a self learning communication module capable of improving the psychomotor domains involved in provision of care. (iii) Measure the improvement in the knowledge and specific skill components of the AWWs with the self learning communication module. Design : Intervention study. Setting : Integrated Child Development Scheme Blocks of Varanasi District. Participants : Anganwadi workers belonging to two ICDS Blocks, one was the intervention group and the control group. Study Variable : Self learning communication module. Outcome Variable : Improvement in the cognitive and psychomotor skills of those workers who were administered the module in comparison with the control group. Statistical Analysis : Students â€˜tâ€ test and paired â€˜tâ€ test. Results: There was a significant improvement (p less than 0.001) in the performance skills between the intervention and the control groups. Conclusion: The training modules was effective in improving the overall performance of the workers. However, repeated inservice training is essential to maintain the levels of improvement.